2009
DOI: 10.3382/japr.2009-00025
|View full text |Cite
|
Sign up to set email alerts
|

Organic poultry: Consumer perceptions, opportunities, and regulatory issues

Abstract: Primary Audience: Researchers SUMMARYOrganic and all-natural foods have become an alternative in most mainstream retail food outlets. Organic foods, although only 3% of total retail food sales, account for an estimated $17 billion in sales in the United States, and this category has been growing at a rate 7 times faster than the average food category, maintaining a sustained growth rate of more than 15% per year. Organic meat is the fastest growing sector of the organic market, and organic poultry is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 7 publications
0
21
0
6
Order By: Relevance
“…Consumers want chickens that provide a high level of nutrition with no contaminants, good flavour and rearing techniques that offer good welfare and health for the bird (Sundrum, 2001;Owens et al, 2006). Indeed, there is a common belief that organic chickens are safer and more nutritious than conventional ones, and therefore an increasing number of consumers are willing to pay a premium for free-range or certified organic chicken meat (Castellini et al, 2008;Crandall et al, 2009). As far as the qualitative characteristics of chicken meat are concerned, there is a controversy as to whether the alternative systems result in better quality and taste than conventional rearing systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consumers want chickens that provide a high level of nutrition with no contaminants, good flavour and rearing techniques that offer good welfare and health for the bird (Sundrum, 2001;Owens et al, 2006). Indeed, there is a common belief that organic chickens are safer and more nutritious than conventional ones, and therefore an increasing number of consumers are willing to pay a premium for free-range or certified organic chicken meat (Castellini et al, 2008;Crandall et al, 2009). As far as the qualitative characteristics of chicken meat are concerned, there is a controversy as to whether the alternative systems result in better quality and taste than conventional rearing systems.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the qualitative characteristics of chicken meat are concerned, there is a controversy as to whether the alternative systems result in better quality and taste than conventional rearing systems. Previous studies suggested that factors such as strain of the bird and type of rearing system have a great impact on meat quality features (Castellini et al, 2002a; b;2008;Quentin et al, 2003;Fanatico et al, 2005;Grashorn 2005;Husak et al, 2008;Crandall et al, 2009). Broilers reared in alternative production systems are encouraged to forage and benefit from the vegetation, thereby increasing their choice of environment and food source (Castellini et al, 2002a;Grashorn, 2005;Husak et al, 2008;Martino et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They also prefer products from systems that provide good welfare and health for the birds (Sundrum, 2001;Owens et al, 2006). Indeed, there is a common belief that organic chicken meat is safer and more nutritious than that of conventional broilers, and therefore, an increasing number of consumers are willing to pay a premium for certified organic chicken meat (Magdeliane & Bloch, 2004;Crandall et al, 2009).…”
Section: Introductionmentioning
confidence: 99%